Near-Infrared Light Regulation of Capture and Release of ctDNA Platforms Based on the DNA Assembly System - Gong, Chaihong; Mao, Xiaowei; Wang, Zhe; Luo, Zhang; Liu, Zhifan; Ben, Yali; Zhang, Weiying; Guo, Zhenzhong (Frontiers in Bioengineering and Biotechnology, 2022)
Despite recent progress, a challenge remains on how to gently release and recover viable ctDNA captured on DNA probe-based devices. Here, a reusable detector was successfully manufactured for the capture and release of ctDNA by means of an UCNPs@SiO2-Azo/CD-probe. Biocompatible NIR light is used to excite UCNPs and convert into local UV light. Continuous irradiation induces a rapid release of the entire ctDNA-probe–CD complex from the functionalized surface via the trans−cis isomerization of azo units without disrupting the ctDNA-structure receptor. Specifically, these composite chips allow reloading DNA probes for reusable ctDNA detection with no obvious influence on their efficiency. The results of our study demonstrated the potential application of this platform for the quantitative detection of ctDNA and the individualized analysis of cancer patients.